Influence of Tinnitus Percentage Index of Speech Recognition in Patients with Normal Hearing - Urnau, Daila; da Silva, Paula Andreta Barros; Seligman, Lílian (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The understanding of speech is one of the most important measurable aspects of human auditory function. Tinnitus affects the quality of life, impairing communication.Objective: To investigate possible changes in the Percentage Index of Speech Recognition (SDT) in individuals with tinnitus have normal hearing and examining the relationship between tinnitus, gender and age.Methods: A retrospective study by analyzing the records of 82 individuals of both genders, aged 21-70 years, totaling 128 ears with normal hearing. The ears were analyzed separately, and divided into control group, no complaints of tinnitus and group study, with complaints of tinnitus. The variables gender and age groups and examined the influence of tinnitus in the SDT. It was considered normal, the percentage of 100% correct and changed, and the value between 88-96%. These criteria were adopted, since the percentage below 88% correct is found in individuals with sensorineural hearing loss.Results: There was no statistically significant difference between the variables age and tinnitus, and tinnitus SDT, only gender and tinnitus. The prevalence of tinnitus in females (56%), higher incidence of tinnitus in the age group 31-40 years (41.67%) and fewer from 41 to 50 years (18.75%) and on the SDT there was a greater percentage change in individuals with tinnitus (61.11%).Conclusion: The buzz does not interfere with SDT and there is no relationship between tinnitus and age, only between tinnitus and gender.
Keywords: hearing; tinnitus; speech intelligibility; speech audiometry; age groups; sex distribution